Exploring Masterweb's Effectiveness in Optimizing Digital Based Learning and Education Management - Tjiptady, Bella Cornelia; Rohman, Mojibur; Rahman, Rifki Zainur; Elmunsyah, Hakkun; Tarecha, Rachmad Imam (Universitas Multimedia Nusantara, 2024)
Masterweb is a concept where multiple web services are integrated into a centralized platform, offering seamless access and management of various online tools and resources. Research discusses the effectiveness of masterweb in optimizing digital-based learning and education management. Research method uses a mix method approach with an exploratory design. Paper also highlights the importance of transforming learning media in the digital era and how digitalization can improve the quality of vocational education. Research results show that the application of Masterweb allows the adoption of blended learning methods that combine conventional approaches with digital elements. Collaboration with expert companies in developing e-learning and multimedia systems also ensures the availability of ICT infrastructure that supports the smooth learning process. With Masterweb, teachers and school management can be more effective in recording teaching and learning activities, monitoring student attendance, and increasing the effectiveness of monitoring and developing student skills. This research provides important insights into the importance of technology integration in education to increase efficiency, effectiveness, management and the attractiveness of learning in the digital era